A novel particle swarm optimization based robust H-infinity control for rotorcrafts. Issue 4 (27th May 2014) - Dai, Jiyang; Ying, Jin; Tan, Chang
Abstract : Purpose: – The purpose of this paper is to present a novel optimization approach to design a robust H-infinity controller. Design/methodology/approach: – To use a modified particle swarm optimization (PSO) algorithm and to search for the optimal parameters of the weighting functions under the circumstance of the given structures of three weighting matrices in the H-infinity mixed sensitivity design. Findings: – This constrained multi-objective optimization is a non-convex, non-smooth problem which is solved by a modified PSO algorithm. An adaptive mutation-based PSO (AMBPSO) algorithm is proposed to improve the search accuracy and convergence of the standard PSO algorithm. In the AMBPSO algorithm, the inertia weights are modified as a function with the gradient descent and the velocities and positions of the particles. Originality/value: – The AMBPSO algorithm can efficiently solve such an optimization problem that a satisfactory robust H-infinity control performance can be obtained.